Antigone's Example: Early Modern Women's Political Writing in Times of Civil War from Christine de Pizan to Helen Maria Williams. - Lucenko, Kristina (Early Modern Women: An Interdisciplinary Journal)
The article discusses Mihoko Suzuki's book, *Antigone's Example*, which explores early modern women's political writing in France and England from the fifteenth to the early nineteenth century. Suzuki employs a comparative and transnational approach to highlight how civil wars and revolutions enabled women to challenge cultural gender norms and engage in political discourse. The book analyzes the works of sixteen women writers, including Christine de Pizan and Margaret Cavendish, demonstrating their contributions to political thought and their roles as political advisors during tumultuous times. Suzuki's research offers valuable insights into the complexities of women's political engagement across different historical contexts and literary forms.